Marketing procedures and profit: A case study on medicinal plants at selected Tamu (Traditional market) in Sabah, Malaysia - Julius Kodoh; Fatin Nur Ain Dzulkarnin; Affendy Hassan; Mandy Maid (UniSE Press, 2021)
Medicinal plants are the main products of the local herbal industry. These plants were identified as the potential sources of economic growth and socio-economic development of the local people. The marketing of medicinal plants in Malaysia has been developing rapidly based on their importance in the Malaysian economy. High-value herbal products have been categorized as one of the 12 National Key Economic Areas in Economics Transformation Program of Malaysia. However, less attention was given to the marketing and trading chain, targeted market, and income sources for the local people. This research was carried out in selected Tamu in Sabah to identify the commonly marketed and traded medicinal plant species; document the part of medicinal plants utilized; identify marketing pattern and market chains of the medicinal plants trade; and investigate the profit margins of the medicinal plant trade. The data were collected from seven major Tamu at seven in districts in Sabah involving face-to-face interview of 64 local traders using a semi-structured questionnaire. A total of 53 species of medicinal plants were traded at these Tamu. The most marketed medicinal plants were Raja kayu (Koompassia malaccensis), Mas cotek (Ficus deltoidea), Kayu panas (Goniothalamus roseus), Jerangau merah (Boesenbergia stenophylla), and Halia merah (Zingiber sp.). The plants were mostly sold as unprocessed raw plants (69.5%). The most utilized part of plants was leaf and fruit. Three (3) channels of the marketing chain were involved, namely, i) self-collected (29.7%); ii) buy directly from collectors (53.1%); iii) buy from middlemen (17.2%). The sellers’ profit margins varied and were mainly affected by the types of marketing chain chosen by the sellers. However, the profit margin contributed significantly to the income of the communities. The average monthly profit margin of selling medicinal plants products by the local traders were 60.33% (RM924.07/USD223.21). The results showed that medicinal plants products have a substantial profit margin, indicating profitable sales for the local traders. This study showed that medicinal plants products have a potential source of income to the local traders involved.